Low-amperage pulsating direct current has a bactericidal effect on marine fish pathogens in circulating seawater - Won Ki Min (2018)
© 2016 Elsevier Ltd The bactericidal effect of pulsating direct current (PC) generated at a very low amperage (0.01 A) with a frequency of 5 Hz or 14 kHz against two marine fish pathogens, Edwardsiella tarda and Vibrio parahaemolyticus, in circulating seawater at 15 and 25 °C in comparison with the effect of direct current (DC) of the same amperage was investigated. The bactericidal effect was directly correlated with the generation of active chlorine species (ACS) and the treatment duration. PC treatment at 14 kHz resulted in complete bacterial inactivation when the ACS level reached 0.11–0.12 mg/L after 45–60 min of treatment. PC treatment at 5 Hz required generation of only 0.03–0.07 mg/L ACS to achieve complete bacterial inactivation, although a slightly longer treatment duration (60–90 min) was needed. DC treatment resulted in complete disinfection within a shorter time (30 min) due to greater ACS production. The bactericidal effect and ACS generation were weaker at the higher temperature (25 °C) due to more rapid evaporation of Cl2gas. The pH of the seawater maintained at ∼8.0. A disinfection study in circulating non-chloride Na2SO4solution at pH 8.0 showed that the electric pulsation did not have notable bactericidal effect up to 14 kHz at 0.2 A.